Effect of Silicate, Carbonate, Calcium Lignosulphonate, and Silicic Acid Additives on Ammonium Nitrate Degradation - Gezerman, A. O. (HRVATSKO DRUSTVO KEMJIJSKIH INZENJERA I TEHNOLOGA, 2020)
Ammonium nitrate is the most commonly used nitrogen fertilizer in the agriculture and plays an important role in the development of leaves and stems in plants. The storage and production of ammonium nitrate at the industrial scale can result in degradation and caking. Various solutions have been proposed, however, to date, an effective solution to the degradation problem has not been identified. The addition of silicic acid during the production of ammonium nitrate prevents the double salt formation caused by sulphuric acid additive, which is a process requirement. Silicic acid was combined with calcium carbonate in the dilution stage in order to increase the fracture strength of ammonium nitrate. With the addition of calcium lignosulphonate, the phase conversion of ammonium nitrate granules was completed more rapidly, and thus the problem of degradation was prevented. Thus, chemical and physical degradation of the ammonium nitrate structure were prevented during the 2-year storage period, which was adopted as the standard for the ammonium nitrate production process.
Keywords: Ammonium nitrate; degradation; caking; calcium lignosulphonate; silicic acid; limestone; STABILITY; PHASE; SOIL; Chemistry